Sequential feeding of β-adrenergic agonists to realimentated cull cows - Weber, Melissa Jean (Kansas State University, 2011)
Sixty cull cows were utilized to investigate the effects of feeding a single or sequence of β-adrenergic agonists (β-AA) on performance, mRNA expression, carcass traits, economics, meat palatability, and ground beef color. Treatments included: 1) concentrate fed for 74 d (C); 2) concentrate fed for 49 d then supplemented with ractopamine-HCl for 25 d (RH); 3) concentrate fed for 51 d then supplemented with zilpaterol-HCl for 20 d (ZH); 4), concentrate fed for 26 d then supplemented with RH for 25 d followed by ZH for 20 d (RH + ZH). No differences existed among treatments for performance or carcass characteristics. However, cows supplemented with ZH (ZH and RH + ZH treatments) had increased LM areas (P = 0.18) compared to control and RH cows. Sequential feeding of RH followed by ZH had no influence on β2-adrenergic receptor (AR) mRNA expression. However, β2-AR mRNA was increased (P < 0.05) in the RH and ZH treatments when RH or ZH was supplemented during the last 20 to 25 d of feeding. Myosin heavy chain (MHC) Type IIa mRNA decreased (P < 0.05) from d 24 to 51 in all cows, while MHC-IIx increased (P < 0.05) in the ZH and RH + ZH treatments during ZH supplementation. No differences were observed in ground beef color shelf-life among treatments. Effects of β-AA supplementation on meat palatability varied among muscles. Infraspinatus steaks had improved (P < 0.05) WBSF values with β-AA supplementation. Psoas major steaks from the RH + ZH treatment were rated as more tender than steaks from all other treatments. Non-enhanced LM steaks from ZH supplemented cows had higher (P = 0.12) WBSF values along with decreased (P < 0.0001) percentages of degraded desmin compared to control and RH cows. Collagen solubility of the LM was increased with ZH supplementation compared to RH and control cows. Enhancement of steaks with 0.1 M calcium lactate improved LM tenderness of β-AA supplemented cows. Implanting and feeding cull cows for 74 d, regardless of β-AA supplementation, added value by transiting cows from a “cull” cow to “white” cow market.
Keywords: realimentation; cull cows; ractopamine-HCl; zilpaterol-HCl; carcass and meat traits; β2-adrenergic receptors; Agriculture, Animal Culture and Nutrition (0475); Agriculture, Food Science and Technology (0359)